Improving the use of early timber inventories in reconstructing historical dry forests and fire in the western United States: Comment - Hagmann, R. Keala; Stevens, Jens T.; Lydersen, Jamie M.; Collins, Brandon M.; Battles, John J.; Hessburg, Paul F.; Levine, Carrie R.; Merschel, Andrew G.; Stephens, Scott L.; Taylor, Alan H.; Franklin, Jerry F.; Johnson, Debora L.; et al. (Ecosphere (Washington, D.C), 2018)
Knowledge of historical forest conditions and disturbance regimes improves our understanding of landscape dynamics and provides a frame of reference for evaluating modern patterns, processes, and their interactions. In the western United States, understanding historical fire regimes is particularly important given ongoing climatic changes and their effects on fire regimes (Miller and Safford , Westerling , Abatzoglou et al. ). Yet, all methods used to reconstruct historical forest conditions have limitations. Confidence in the results generated by any single method increases when multiple studies, using diverse methods, converge on comparable results. Early timber inventories in western ponderosa pine and mixed‐conifer forests (Collins et al. , Hagmann et al. , , Collins et al. , Stephens et al. , Hagmann et al. ) document forest conditions that are consistent with other records and reconstructions of historical vegetation patterns and fire regimes on landscapes that experienced frequent low‐ to moderate‐severity fires. In a recent assessment of early timber inventories, Baker and Hanson () (hereafter B&H) concluded that these inventories of large forest landscapes in the Central and Southern Sierra Nevada in California and the eastern slopes and foothills of the Cascade Range in Oregon systematically underestimated historical tree density and were biased toward areas of large, merchantable trees. Here, we document serious errors in B&H due to the following: (1) biased estimates of historical tree density from land‐survey data; (2) incorrect assumptions about the accuracy of early timber inventories; (3) inappropriate comparisons of studies of vastly different spatial scales, forest types, and diameter limits; (4) unsubstantiated criticism of bias in early timber inventories; and (5) inappropriate cross‐referencing and misrepresentation of high‐severity fire in historical records.